Eco-friendliness of Iran's digital services and information technology industry in the web hosting and cloud services sectors - Mozhdeh Rezvani Kashani; Seyed Hossein Hashemi; Mahdi Mohammadi (علوم محیطی)
Introduction: Due to the growth and development of new types of communication and information technologies around the world, the use of digital services is widely increasing and our country, Iran, is no exception to this rule. Information technology and digital services industries consume significant amounts of energy in various forms as well as in various sectors such as production, distribution and use of relevant equipment and services and as a result, produce various pollutants, including greenhouse gases, and release them into the environment. Therefore, the purpose of this study is to investigate the eco-friendliness of digital services and IT industry of Iran in the web hosting and cloud services sectors through evaluating the north-west data center of Iran as a representative of the IT industry of Iran in the web hosting and cloud services sectors.Material and methods: For this purpose, in this study, first the effective aspects of information technology on the environment as well as the environmental standards related to data centers were identified through library studies and review of existing domestic and foreign literature and after that, eight servers of “Iran Server” were investigated. In the next step, after estimating the amount of energy consumed and carbon dioxide produced by the north-west data center of Iran (which has 319 active servers), the efficiency and environmental compatibility metrics of this data center were calculated and finally, by analyzing and summarizing the obtained results, eco-friendliness of the north-west data center of Iran as a representative of IT industry of Iran in the web hosting and cloud services sectors, was investigated.Results and discussion: The results of energy consumption and pollutants production of the north-west data center of Iran indicated that this data center consumes an average of 185.16 MWh of electricity per month, and followed by that produces 533.26 tons of carbon dioxide per month. Also, the values of Carbon Usage Effectiveness (CUE), Power Usage Effectiveness (PUE) and Energy Reuse Effectiveness (ERE) metrics in this data center were equivalent to 2.88 (kg CO2 per kilowatt hour), 4.03 and 4.03, respectively, and also the values of Energy Reuse Factor (ERF) and Green Energy Coefficient (GEC) were zero. These values indicate that the energy consumption of Iran's data centers is supplied from non-renewable energy sources and this energy is finally released in the form of excess heat in the environment after consumption in different sectors, which emits a large amount of greenhouse gases including CO2 in the environment and inflicts numerous and irreparable damages on the environment such as air pollution, global warming, climate change, etc.Conclusion: A general summary of the information obtained from the study of various aspects of the eco-friendliness of the north-west data center of Iran as a representative of the IT industry of Iran in the web hosting and cloud services sectors and its comparison with other green data centers in the world shows, this data center has not met the necessary metrics to comply with environmental standards related to green or eco-friendly data centers and as a result is not very compatible with the environment and is far from other green data centers in the world.